Palladium-catalyzed decarboxylative ortho-arylation of 2-pyridyl sulfoxides with benzoyl peroxides. Issue 45 (1st November 2016) - Sun, Meng; Wang, Zhe; Wang, Jiaxin; Guo, Peiyu; Chen, Xiangxiang; Li, Ya-Min
Abstract : A palladium catalyzed efficient strategy for regio-selective ortho -arylation of sulfoxides with aryl acyl peroxides via decarboxylation has been developed. Abstract : A palladium catalyzed efficient strategy for regio-selective ortho -arylation of sulfoxides with benzoyl peroxides via decarboxylation has been developed. This reaction proceeds smoothly, tolerates a variety of functional groups, and provides easy access to the synthesis of different biaryl compounds.